Free Amino Acids in Human Milk: A Potential Role for Glutamine and Glutamate in the Protection Against Neonatal Allergies and Infections - van Sadelhoff, Joris H. J.; Wiertsema, Selma P.; Garssen, Johan; Hogenkamp, Astrid (Frontiers in Immunology, 2020)
Breastfeeding is indicated to support neonatal immune development and to protect against neonatal infections and allergies. Human milk composition is widely studied in relation to these unique abilities, which has led to the identification of various immunomodulating components in human milk, including various bioactive proteins. In addition to proteins, human milk contains free amino acids (FAAs), which have been not been well-studied. Of those, the FAAs glutamate and glutamine are by far the most abundant. Levels of these FAAs in human milk sharply increase during the first months of lactation, in contrast to most other FAAs. These unique dynamics are globally consistent, suggesting that their levels in human milk are tightly regulated throughout lactation and, consequently, that they might have specific roles in the developing neonate. Interestingly, free glutamine and glutamate are reported to exhibit immunomodulating capacities, indicating that these FAAs could contribute to neonatal immune development and to the unique protective effects of breastfeeding. This review describes the current understanding of the FAA composition in human milk. Moreover, it provides an overview of the effects of free glutamine and glutamate on immune parameters relevant for allergic sensitization and infections in early life. The data reviewed provide rationale to study the role of free glutamine and glutamate in human milk in the protection against neonatal allergies and infections.